Implications of anti-Ro/Sjögren's syndrome A antigen autoantibody in normal sera for autoimmunity. - Gaither, K K (1987)
We have applied a sensitive assay to analyze lupus and Sjögren's syndrome autoantibodies in 40 normal sera. Seven of these bound Ro/Sjögren's syndrome A antigen (SSA). Although this binding was 1,000-fold lower than the highest anti-Ro/SSA level measured from patients, it was inhibited by human Ro/SSA. Positive normal serum-bound Ro/SSA in Western immunoblots and binding activity was demonstrated in the F(ab')2 fragment of IgG. Affinity purification of normal anti-Ro/SSA IgG increased the specific anti-Ro/SSA binding by greater than 17-fold. This purified antibody formed a Ro/SSA precipitin and had a relative affinity for Ro/SSA identical to that of Ro/SSA precipitin-positive patients. These data demonstrate that the anti-Ro/SSA present in healthy normal donors is true autoantibody. Anti-La/Sjögren's syndrome B antigen (SSB) autoantibodies were found in 3 of the 40 normal sera, while none bound nuclear ribonucleoprotein (Sm). Finding low levels of anti-Ro/SSA and anti-La/SSB among normals may indicate that anti-Ro/SSA and anti-La/SSB occur in disease by enhancement of a preexisting immune response.